2017
DOI: 10.3178/hrl.11.24
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on climate change impact on precipitation and floods in Asian river basins

Abstract: Abstract:As many water related disasters occur frequently around the world, proper assessment of future climate change impact on floods and droughts is essential. In this study, we focused on basin-scale climate change impact assessment as necessary information for studying adaptation measures on the basis of integrated water resources management. We used Meteorological Research Institute-Atmospheric General Circulation Model (MRI-AGCM) 3.2S (20 km grid super high resolution model) and a series of simulation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Kure and Tebakari, 2012;Iwami et al, 2017) due to climate change. Iwami et al (2017) reported that the Solo River basin, located on the east side of Java Island, will become wet in the future, with more inundation areas and specific peak discharges in extreme flood events.…”
Section: Future Projection Of Flood Inundationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kure and Tebakari, 2012;Iwami et al, 2017) due to climate change. Iwami et al (2017) reported that the Solo River basin, located on the east side of Java Island, will become wet in the future, with more inundation areas and specific peak discharges in extreme flood events.…”
Section: Future Projection Of Flood Inundationmentioning
confidence: 99%
“…Kure and Tebakari, 2012;Iwami et al, 2017) due to climate change. Iwami et al (2017) reported that the Solo River basin, located on the east side of Java Island, will become wet in the future, with more inundation areas and specific peak discharges in extreme flood events. However, this was not considered in the present study because, as reported by Budiyono et al (2016), the impact of climate change on floods in Jakarta may be much smaller than that of land-use changes and land subsidence.…”
Section: Future Projection Of Flood Inundationmentioning
confidence: 99%
“…Based on previous literature, Blöschl et al [2] hypothesized the impact of climate and land-use/land-cover changes on hydrological response as a function of catchment scale as shown in Figure 1, which shows that sudden changes in the watershed response can occur due to land use/land cover change [3]. The impact of climate change on magnitude and frequency of floods has been widely investigated [4][5][6]. Similarly, numerous researches focused on study on the impacts of land cover changes on watershed hydrological response [3,[7][8][9], however, only a few of them focused on analyzing the impact of land-cover change in river floods using distributed hydrological modeling [7].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the simulations in these studies have a good agreement with the observed hydrological data and satellite-derived flood map extent. The effects of land use and climate change on flood behavior were also investigated using the RRI model [38,39]. None of these studies, however, used Global Precipitation Measurement (GPM) data in the RRI model.…”
Section: Introductionmentioning
confidence: 99%